Fluency and confidence predict paramedic diagnostic intuition: An experimental study of applied dual-process theory. (March 2022) - Keene, Toby; Pammer, Kristen; Lord, Bill; Shipp, Carol
Highlights: Objective likelihood is associated with intuition in paramedics and students. The speed the answer came to mind and confidence predicted intuitive responses. This method can be used for future studies into paramedic decision making. Abstract: Introduction: We report an experiment using Australian paramedics (n = 64) and Australian paramedicine undergraduates (n = 44), on the processes underlying the formation of an intuitive diagnostic impression, based on limited dispatch information. Previous research has signalled roles for objective likelihood of the disease, subjective typicality of the disease, and the ease with which the diagnosis comes to mind (answer fluency) as important in impression formation. Method: Participants completed four brief written clinical vignettes under time pressure and with a concurrent navigation task to simulate conditions faced by paramedics prior to meeting a patient. Diagnostic impression, confidence and subjective typicality of the vignette were self-reported while answer fluency was measured. The vignettes varied the objective likelihood of a diagnosis of Acute Coronary Syndrome (ACS), a condition often encountered by paramedics. Results: Likelihood, answer fluency, self-reported typicality and confidence predicted the impression but there was no effect of experience. Students and experienced paramedics had comparable accuracy and performance. Conclusion: The results support a role for answer fluency and confidence in forming that impression. We have shown it is possible to experimentally manipulate various factors associated with paramedic diagnostic impressions. These experimental methods can form the basis for additional studies into paramedic decision making.